White Matter Integrity Predicts Electrical Stimulation (tDCS) and Language Therapy Effects in Primary Progressive Aphasia. (January 2021) - Zhao, Yi; Ficek, Bronte; Webster, Kimberly; Frangakis, Constantine; Caffo, Brian; Hillis, Argye E.; Faria, Andreia; Tsapkini, Kyrana
Background: Transcranial direct current stimulation (tDCS), in conjunction with language therapy, improves language therapy outcomes in primary progressive aphasia (PPA). However, no studies show whether white matter integrity predicts language therapy or tDCS effects in PPA. Objective: We aimed to determine whether white matter integrity, measured by diffusion tensor imaging (DTI), predicts written naming/spelling language therapy effects (letter accuracy on trained and untrained words) with and without tDCS over the left inferior frontal gyrus (IFG) in PPA. Methods: Thirty-nine participants with PPA were randomly assigned to tDCS or sham condition, coupled with language therapy for 15 daily sessions. White matter integrity was measured by mean diffusivity (MD) and fractional anisotropy (FA) in DTI scans before therapy. Written naming outcomes were evaluated before, immediately after, 2 weeks, and 2 months posttherapy. To assess tDCS treatment effect, we used a mixed-effects model with treatment evaluation and time interaction. We considered a forward model selection approach to identify brain regions/fasciculi of which white matter integrity can predict improvement in performance of word naming. Results: Both sham and tDCS groups significantly improved in trained items immediately after and at 2 months posttherapy. Improvement in the tDCS group was greater and generalized to untrained words. White matter integrity of ventral language pathways predicted tDCS effects in trained items whereas white matter integrity of dorsal language pathways predicted tDCS effects in untrained items. Conclusions: White matter integrity influences both language therapy and tDCS effects. Thus, it holds promise as a biomarker for deciding which patients will benefit from language therapy and tDCS.